2019
DOI: 10.1002/btpr.2953
|View full text |Cite
|
Sign up to set email alerts
|

Insights into virus inactivation by polysorbate 80 in the absence of solvent

Abstract: Triton X‐100 has long been used either alone or in combination with solvent to inactivate enveloped viruses in biopharmaceutical manufacturing. However, European Chemicals Agency (ECHA) officially placed Triton X‐100 on the Annex XIV authorization list in 2017 because 4‐(1,1,3,3‐tetramethylbutyl) phenol, a degradation product of Triton X‐100, is of harmful endocrine disrupting activities. As a result, any use of Triton X‐100 in the European Economic Area would require an ECHA issued authorization after the sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…This issue has led biopharmaceutical manufacturers to search for more environmentally friendly detergents that can replace TX-100 while displaying functionally equivalent virus inactivation properties [ 9 , 10 , 11 ]. Accordingly, to test detergent candidates, the major focus has been on treating selected membrane-enveloped viruses with different detergent concentrations under varying environmental conditions and exposure times and measuring the resulting effects on viral infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has led biopharmaceutical manufacturers to search for more environmentally friendly detergents that can replace TX-100 while displaying functionally equivalent virus inactivation properties [ 9 , 10 , 11 ]. Accordingly, to test detergent candidates, the major focus has been on treating selected membrane-enveloped viruses with different detergent concentrations under varying environmental conditions and exposure times and measuring the resulting effects on viral infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…No assays above 668 μg/mL were performed because the high concentrations of the Tween 80 and ethanol mixture, which were shown to generate a total cytotoxicity in Vero 76. Moreover, essential forming protein-lipid complexes, avoiding the entry of the viral genome inside the host by adsorption (28,29). Additionally, high temperatures generate faster virus inactivation due to accelerated hydrolysis of PS80 and subsequent interactions between oleic acid and the viral envelope (29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, essential forming protein-lipid complexes, avoiding the entry of the viral genome inside the host by adsorption (28,29). Additionally, high temperatures generate faster virus inactivation due to accelerated hydrolysis of PS80 and subsequent interactions between oleic acid and the viral envelope (29). With respect to the solvent, ethanol induces the activity of the enzyme 2",5" oligoadenylate synthetase whose principal role is to promote cellular resistance against viral infection (developing an antiviral state).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to identify the components leading to oleic acid production from PS-80 for virus inactivation, Chen et al. evaluated CHO cell lines that had one to four lipase/esterase genes knocked out through genetic disruption [ 57 ]. It was observed that PS-80 was still able to inactivate virus, albeit to somewhat reduced efficiency, in the cell-free culture harvests from these genetically engineered CHO cell lines, including the quadruplet knockout CHO.…”
Section: Control Strategymentioning
confidence: 99%